Analysis of Channels and Marketing Margins, Horticultural Farmers in West Tobelo Sub-District, North Halmahera - Zeth Patty; Ariance Yeane Kastanja (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
The study conducted at the Farmers Group in Sukamaju Village, West Tobelo District aims to find out the marketing channels of several horticultural products in West Tobelo District and analyze marketing margins and farmer shares received by farmers. The benefits of this research are to provide an overview of information for the community and farmers about channels, marketing margins and parts received by farmers from the marketing of horticultural commodities in Tobelo Barat District. The study was conducted by the interview method using a list of questions. The data collected includes commodity prices at the farm level, prices at the collecting level, prices for consumers, as well as marketing institutions involved in the marketing process. Marketing channel data are analyzed schematically, while marketing margins and margin share are calculated by comparing the selling prices of farmers and the selling price of consumers. The results showed that there were 3 horticultural product marketing channels in farmer groups in West Tobelo, namely 0 level channels and 1-level channel for watermelon and bitter commodity, as long as tomatoes there were channels, namely 2-level marketing channels. The biggest marketing margin is found in the marketing of good quality tomato commodities of Rp.13,000/kg, while Pare marketing gives the lowest marketing margin value of Rp.4,000/kg. The biggest margin share in the marketing channel type 1 (0 level) for all marketed commodities.